Intranasal octenidine and universal antiseptic bathing reduce methicillin-resistant Staphylococcus aureus (MRSA) prevalence in extended care facilities. Issue 16 (4th December 2018) - Chow, A.; Hon, P. Y.; Tin, G.; Zhang, W.; Poh, B. F.; Ang, B.
Abstract: Intranasal octenidine, an antiseptic alternative to mupirocin, can be used for methicillin-resistant Staphylococcus aureus (MRSA) decolonisation in the prevention of nosocomial transmission. A controlled before–after study was conducted in three extended-care hospitals in Singapore. All inpatients with >48 h stay were screened for MRSA colonisation in mid-2015(pre-intervention) and mid-2016(post-intervention). Hospital A: universal daily chlorhexidine bathing throughout 2015 and 2016, with intranasal octenidine for MRSA-colonisers in 2016. Hospital B: universal daily octenidine bathing and intranasal octenidine for MRSA-colonisers in 2016. Hospital C: no intervention. In 2015, MRSA prevalence was similar among the hospitals (Hospital A: 38.5%, Hospital B: 48.1%, Hospital C: 43.4%, P = 0.288). From 2015 to 2016, MRSA prevalence reduced by 58% in Hospital A (Adj OR 0.42, 95% CI 0.20–0.89) and 43% in Hospital B (Adj OR 0.57, 95% CI 0.39–0.84), but remained similar in Hospital C (Adj OR 1.19, 95% CI 0.60–2.33), after adjusting for age, gender, comorbidities, prior MRSA carriage, prior antibiotics exposure and length of hospital stay. Compared with the change in MRSA prevalence from 2015 to 2016 in Hospital C, MRSA prevalence declined substantially in Hospital A (Adj OR 0.35, 95% CI 0.13–0.97) and Hospital B (Adj OR 0.48, 95% CI 0.22–1.03). Topical intranasal octenidine, coupled with universal daily antiseptic bathing, can reduce MRSA colonisation in extended-care facilities.